The Severity of Head Injuries Based on Injury Location: a Cross-Sectional Study - Erik Irham Lutfi; Meirna Eka Fitriasnani; Hengky Irawan; Achmad Wahdi; Ely Isnaeni (Universitas STRADA Indonesia, 2025)
Background: The mortality and morbidity rates in patients with traumatic head injuries are still high, caused by primary damage due to internal bleeding. Intracerebral hemorrhage is a common complication of traumatic brain injury. The severity of head injury patients is a predisposing factor that causes high mortality and morbidity rates. The presence of bleeding in the head affects the severity of the patient's injury, bleeding in the head will reduce blood flow to the head, which will cause decreased blood perfusion to the brain. In severe head injury, a hematoma of more than 50 mL is associated with higher mortality. Acute ICH (Intra Cerebral Haemoraghea) can be a catastrophic event with the mortality largely predicted by the hematoma size, location, and the patients' GCS (Glasgow Coma Scale) on admission. Objective: This study aims to determine the relationship between the location of intracerebral hemorrhage and the severity of head injury. Methods: This study uses a correlational analytical approach with a cross-sectional design, utilizing secondary data from medical records of patients with traumatic head injuries from January to December 2022. The calculation of severity using RTS (Revised Trauma Score). These three scores (Glasgow Coma Scale, Systolic Blood Pressure, Respiratory Rate) are then used to take the weighted sum by RTS = 0.9368 GCSP + 0.7326 SBPP + 0.2908 RRP Values for the RTS are in the range 0 to 7.8408. Scores range from 0-4. The study population was patients with moderate to severe traumatic head injuries. Data were analyzed using a correlation test based on Spearman's rank correlation. Results: The results showed a significant relationship between the location of head trauma lesions and the severity of head injury patients (p value = 0.008, correlation coefficient 0.378). Conclusion: Mortality and morbidity rates in patients with traumatic head injuries are still high, caused by primary damage due to internal bleeding. The majority of patient with Trauma brain Injury is male and were in the productive age range ranging from 12-35 years. Epidural hematoma (EDH) is one of the most life-threatening lesions in patients with craniocerebral disease.